Marketing; Past, Present and Future - Mohammad Arief (Trunojoyo University of Madura, 2014)
Marketing is a dynamic concept. Since introduction a few decades ago, the marketing concept has been experience a rapid development. Beginning from the industrial revolutin In 1920, marketing concepts focuses on the production concept, and on the present, marketing concept has been emphasis on how the firm is able to meet the needs and desires of the customer. This article would like to trace the marketing thought history since it was first introduced, present and how the development for the future.